FROM CLASSROOM TO COMMUNITY: CULTURAL IDENTITY FORMATION IN ODISHA’S SHISHU VIDYA MANDIRS - Jena, Saswati; Dash, Diptishree; Saktinanda , Guddi; Dhal, Nibedita (ShodhKosh: Journal of Visual and Performing Arts, 2025)
This article examines how Shishu Vidya Mandirs (SVMs) in Odisha contribute to cultural identity formation among school children. Based entirely on secondary sources, it draws from existing research on indigenous education, cultural pedagogy, and nationalist schooling to explore how these institutions embed Bharatiya values through curriculum, rituals, and symbolic practices. SVMs aim to foster moral development and national pride by integrating Vedic traditions, Sanskritised teachings, and community-based festivals into everyday school life. Positioned as culturally rooted alternatives to mainstream education, they seek to strengthen local identities while aligning students with a broader Hindu-nationalist vision. However, this emphasis on a singular cultural narrative raises important questions about inclusivity and the representation of diverse communities, especially tribal and minority groups. The article calls for a more pluralistic approach to culturally responsive education that respects India’s rich diversity while maintaining the strengths of traditional value-based learning.